Modern globalization and its impacts on the Muslim world - Abdul Razak, Mohd Abbas; Mustapha, Maziah (IIUM Press, 2025)
Long before the coming of modern globalization from the West, Muslims had their version of globalization. The Muslim globalization happened during the peak of the Islamic civilization (750-1258). Interestingly, the golden era of the Muslim Civilization benefited the West in many ways. The scholastic works of Muslim scientists, scholars and philosophers enriched Western civilization immensely, particularly in the areas of science and technology. The fall of Muslim empires gave way to the flourishing of modern globalization which started during the era of Western colonization of the East and Africa. In modern times, the use of the Internet and other modern electronic media directly or indirectly has sped up the process of transporting modern globalization to every nook and cranny of the globe. Since modern globalization is mainly coming from the West, this chapter intends to explore and investigate in what ways Muslim globalization is different when compared to modern globalization, to look into some of the meanings attached to modern globalization, the shifting aims of education, the marginalization of local culture and languages, the brain drain phenomenon that happens due to globalization, how Muslims should react to globalization and finally on the question, as to whether Western globalization can be equated to re-colonization of the East and Africa.